Repositioning Error Compensation in Discontinuous Ground-Based SAR Monitoring - Cheng Hu; Jiaxin Zhu; Yunkai Deng; Weiming Tian; Peng Yin (Remote Sensing, 2021)
The discontinuous mode of ground-based synthetic aperture radar (GB-SAR) is suitable for monitoring creep landslides. However, the instrument needs to be installed and disassembled repeatedly, which could inevitably cause repositioning error, and severely affect the accuracy of deformation measurements. This paper performs a detailed theoretical analysis of the repositioning error based on the Taylor expansion of a ternary function, and it can be built as a linear multi-parameter model. Simulations are made to validate the effectiveness of this model compared with two common first-order and second-order models. Then a compensation method based on the permanent scatterer (PS) technique is proposed. Two experiments of discontinuous monitoring are discussed. The first one is an equivalent discontinuous experiment, which utilizes two corner reflectors to evaluate the compensation accuracy. The other one is a discontinuous experiment taken on a steep mountain. Compared with the common methods, the proposed method can better compensate for the error phase and benefit high-precision deformation monitoring.